A study of factors affecting USM students' performance in primary master of medicine (anaesthesiology) conjoint examination - Yusoff, Ahmad Tajuddin Mat (2020)
Objectives The aim of study was to determine the factors affecting USM students’ performance in their Primary M. Med (Anaest) Conjoint Examination in terms of academic background, environmental and socio-economic factors. Methods This was a cross-sectional, simple sampling study, involving 73 subjects, who passed Postgraduate Primary M. Med (Anaest) Conjoint Exam either at first or subsequent attempts. They were divided into two groups; 1) Group 1: Candidates who passed at first attempt and 2) Group 2: Candidates who passed after subsequent repeat exam. The subjects were required to respond to self-administered questionnaires. Results Out-campus candidates who worked outside Peninsular Malaysia had higher chance to pass at first attempt by 81% (adjusted OR 0.19: 95% CI 0.04-0.99), p=0.048). Small discussion group during study leave also increased the chance to pass at first attempt by 41% (adjusted OR 0.59: 95% CI 0.39-0.90), p=0.013). However, longer years in medical services (adjusted OR 1.62: 95% CI 1.03, 2.54, p=0.036) and spouse from nonhealthcare profession (adjusted OR 6.56: 95% CI 1.57, 27.54, p=0.010) lowered the chance to pass at first attempt. Conclusion Out-campus training outside Peninsular Malaysia and discussion group during study leave were significant factors led to higher chance of first attempt success in the exam. The duration in medical services and background of spouse occupation were the significant factors that lowered the chance to pass at first attempt.